2018
DOI: 10.1088/1361-6528/aabb9d
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of physiological fluids to provide insight into the characterization, fate, and biological interactions of silver nanoparticles

Abstract: Silver nanoparticles (AgNPs) are being increasingly utilized in consumer and medical applications. However, there remains conflicting reports on their safety, which are evaluated through a combination of in vitro and in vivo exposure models. These discrepancies may arise, in part, due to the inherent differences between cell-based and animal systems. It is well established that nanotoxicological effects are highly dependent on the unique physicochemical properties and behavior of the particle set, including si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…AgNPs are incorporated into products or materials that are encountered daily such as water filters, fabrics, deodorants, printer ink, toothpaste, food packaging and cosmetics [3,4,5,6]. This degree of public exposure is worrisome, given that the safety of AgNPs has never been fully established and their acute and chronic toxicity remain conflicting [7,8,9]. The unregulated use of AgNPs could be a real risk, not only to public health and environment but also to the economic growth of a number of industries.…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs are incorporated into products or materials that are encountered daily such as water filters, fabrics, deodorants, printer ink, toothpaste, food packaging and cosmetics [3,4,5,6]. This degree of public exposure is worrisome, given that the safety of AgNPs has never been fully established and their acute and chronic toxicity remain conflicting [7,8,9]. The unregulated use of AgNPs could be a real risk, not only to public health and environment but also to the economic growth of a number of industries.…”
Section: Introductionmentioning
confidence: 99%
“…As AgNPs are known to induce mammalian cytotoxicity [ 8 , 9 , 10 , 11 ], the first endpoint assessed was cellular viability, as a function of flow condition ( Figure 3 ). Starting with the A549s ( Figure 3 A), the lower AgNP dosage produced a slight cytotoxic response.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, AgNPs have been linked to potential health concerns, with exposure resulting in significant cytotoxicity [ 7 ]. In addition to cellular death, AgNP exposure has been shown to induce numerous bioeffects including augmented oxidative stress, activation of the inflammatory and immune responses, alterations to signal transduction pathways, and genetic modifications [ 8 , 9 , 10 , 11 ]. For example, a study by Comfort et al demonstrated that, even at dosages in the pg/mL range, AgNPs were able to disrupt normal cell homeostasis by augmenting cellular stress, activating Akt and Erk signal transduction pathways, stimulating pro-inflammatory cytokine secretion, and regulating gene expression [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This intracellular compartment contains both chelators and precipitators known to influence solubility (Kreyling 1992), and an environment in which a number of conditions are engaged to digest the phagocytosed material. This includes a drop in pH to acidic conditions, stimulation of proteolytic lysosomal enzymes, and production of ROS to aid digestion or act as signalling molecules (generating the oxidative/respiratory burst) (Nyberg et al 1989b;Collier et al 1992;Kreyling 1992;Oberd€ orster 1993;Breitner et al 2018).…”
Section: Intracellular Compartmentsmentioning
confidence: 99%
“…The composition of Gamble's solution, and other fluids used to simulate the neutral pH extracellular environment of the lung, is given in Table 1. Gamble's solution has been used in conjunction with other fluids, and can be found in the assessment of many materials, including man-made mineral fibres (MMMF) (Zoitos et al 1997;Guldberg et al 1998;Sebastian et al 2002), Be ore materials (bertrandite, beryl, BeSO 4 , BeO) (Deubner et al 2011), Ag NPs (Breitner et al 2018), rare earth elements (e.g. Ce, La, Nd and Gd) in refinery emissions (Gao et al 2020) and polycyclic aromatic hydrocarbons (PAHs) in coal-related particulate matter (Gao et al 2019).…”
Section: Gamble's Solutionmentioning
confidence: 99%